Implementation of Intra Uterine Device and Implant Family Planning in Batang Gadis Village Jae Sub-District Panyabungan Barat District Mandailing Natal - Helmi Wardah Nasution; Ferika Desi; Risma; Samsidah; Mariani Riska (IJCS: International Journal of Community Service, 2022)
Contraceptives are very useful in family planning programs, but it should be noted that not all contraceptives are suitable for everyone's condition. For this reason, each individual must be able to choose a contraceptive that is suitable for himself. Most family planning acceptors choose and pay for the various contraceptive methods available. Other factors that influence the choice of contraceptive type include partner factors (age, lifestyle, desired family size, experience with past contraceptive methods), health factors (health status, menstrual history, family history, physical examination, pelvic examination), factors contraceptive method (effectiveness, side effects, cost), education level, knowledge, family welfare, religion, and support from husband/wife. These factors will also affect the success of the family planning program. This is because each method or contraceptive chosen has different effectiveness. Therefore, the authors are interested in compiling a paper on Intra Uterine Device (IUD) and Implant contraception.